Examining the impact of growth mindset and lifelong learning on teacher performance among university faculty: The mediating role of professional development - Yuqiao Luo; Yu Bi; Lingjie Wang (PLoS ONE, 2026)
Based on social constructivist learning theory, this study constructs a structural model with teacher growth mindset and lifelong learning as independent variables, teacher professional development as a mediating variable, and teacher performance as the dependent variable, aiming to explore how cognitive beliefs and behavioral tendencies jointly influence teacher performance. Through a questionnaire survey of 620 university teachers and empirical testing using structural equation modeling (SEM), results show that growth mindset and lifelong learning are positively associated with teacher performance. Moreover, teacher professional development functions as an associational mediator linking both growth mindset and lifelong learning with performance. Given the cross-sectional design, these findings reflect statistical associations rather than causal effects. The research findings expand the theoretical model of factors influencing teacher performance and provide practical references for optimizing teacher professional development pathways and university human resource management.